2022
DOI: 10.7717/peerj.13803
|View full text |Cite
|
Sign up to set email alerts
|

Somatization symptoms—prevalence and risk, stress and resilience factors among medical and dental students at a mid-sized German university

Abstract: Objective Previous studies have shown that an increased prevalence of mental illness can be found among medical and dental students. Among these, somatization symptoms are severely understudied. The present study examined the prevalence of somatization symptoms in a subpopulation of medical and dental students and aimed at finding associated risk and resilience factors. Methods A cross-sectional survey was conducted using a self-reporting q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 76 publications
1
8
0
1
Order By: Relevance
“…Five studies assessed factors that have the potential to be helpful in predicting, preventing or treating mental health-related somatic symptoms in medical students; one of these performed an intervention. The four non-interventional factors were resilience [ 37 ], social support [ 38 ], coping strategies [ 58 ] and trait mindfulness [ 48 ]; the interventional study [ 43 ] also assessed mindfulness, and was based on Jon Kabat-Zinn’s Mindfulness-Based Stress Reduction (MBSR) program [ 75 , 76 ]. Resilience was measured with a binary ‘yes/no’ scale on dimensions of resiliency as conceptualized by the authors: use of relaxation techniques, satisfaction with academic studies, religiosity, eating habits, physical activity, musical instrument practice and emotional/social support [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Five studies assessed factors that have the potential to be helpful in predicting, preventing or treating mental health-related somatic symptoms in medical students; one of these performed an intervention. The four non-interventional factors were resilience [ 37 ], social support [ 38 ], coping strategies [ 58 ] and trait mindfulness [ 48 ]; the interventional study [ 43 ] also assessed mindfulness, and was based on Jon Kabat-Zinn’s Mindfulness-Based Stress Reduction (MBSR) program [ 75 , 76 ]. Resilience was measured with a binary ‘yes/no’ scale on dimensions of resiliency as conceptualized by the authors: use of relaxation techniques, satisfaction with academic studies, religiosity, eating habits, physical activity, musical instrument practice and emotional/social support [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…The four non-interventional factors were resilience [ 37 ], social support [ 38 ], coping strategies [ 58 ] and trait mindfulness [ 48 ]; the interventional study [ 43 ] also assessed mindfulness, and was based on Jon Kabat-Zinn’s Mindfulness-Based Stress Reduction (MBSR) program [ 75 , 76 ]. Resilience was measured with a binary ‘yes/no’ scale on dimensions of resiliency as conceptualized by the authors: use of relaxation techniques, satisfaction with academic studies, religiosity, eating habits, physical activity, musical instrument practice and emotional/social support [ 37 ]. High scores on these dimensions of resiliency were found to be significantly correlated with the SOMS-2 somatization index, such that students with higher resiliency had significantly lower somatization ( r s = −0.207, p < .001) [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study also found that third-year students experienced a higher degree of perceived stress than first-year students. Another study found that the rates of depression, anxiety, and stress disorders among medical students were equivalent to the public at the beginning of medical school but deteriorated during their depression (Feussner et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Studies have found that 54.3% of patients diagnosed with somatoform disorders will have an additional diagnosis within twelve months, such as anxiety and depression. Patients with somatoform disorders have a 24% likelihood of suicidal ideation and a 17.6% likelihood of attempting suicide [7], [8].…”
Section: Introductionmentioning
confidence: 99%